2012
DOI: 10.1093/hmg/dds192
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic markers of prostate cancer in plasma circulating DNA

Abstract: Epigenetic differences are a common feature of many diseases, including cancer, and disease-associated changes have even been detected in bodily fluids. DNA modification studies in circulating DNA (cirDNA) may lead to the development of specific non-invasive biomarkers. To test this hypothesis, we investigated cirDNA modifications in prostate cancer patients with locally confined disease (n = 19), in patients with benign prostate hyperplasias (n = 20) and in men without any known prostate disease (n = 20). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 69 publications
0
32
0
1
Order By: Relevance
“…The ability to detect cancer or estimate cancer risk from normal tissue, stool, peripheral blood, or other body fluids (such as sputum and urine) has become the holy grail of biomarker discovery. 342 Biomarkers in normal tissue, stool, or body fluids can represent: 1) a pathological outcome, analogous to established serum tumor markers; 2) a surrogate or shared indicator of etiologic exposure and disease predisposition; or 3) an intermediary in a causal pathway from etiology to downstream outcome (cancer incidence or behavior). Analysis of normal tissue, stool, and body fluids can expand the scope of, and add a novel dimension to MPE research (Figure 3).…”
Section: Analysis Of Normal Tissue Stool Blood or Other Body Fluidsmentioning
confidence: 99%
“…The ability to detect cancer or estimate cancer risk from normal tissue, stool, peripheral blood, or other body fluids (such as sputum and urine) has become the holy grail of biomarker discovery. 342 Biomarkers in normal tissue, stool, or body fluids can represent: 1) a pathological outcome, analogous to established serum tumor markers; 2) a surrogate or shared indicator of etiologic exposure and disease predisposition; or 3) an intermediary in a causal pathway from etiology to downstream outcome (cancer incidence or behavior). Analysis of normal tissue, stool, and body fluids can expand the scope of, and add a novel dimension to MPE research (Figure 3).…”
Section: Analysis Of Normal Tissue Stool Blood or Other Body Fluidsmentioning
confidence: 99%
“…This feature could correspond well with tumor activity. Thus, CCFDNA can be an important noninvasive and useful biomarker especially for follow up in patients with prostate cancer [215218]. …”
Section: Neoplasmsmentioning
confidence: 99%
“…Cortese et al studied circulating free DNA in prostate cancer patients [3]. In this study, circulating DNA (ctDNA) modifications collected from prostate cancer patients with locally confined disease (19 patients), in patients with benign prostate hyperplasias (20 patients), and in men without any known prostate disease (20 patients) were studied after isolation of ctDNA from plasma.…”
Section: Dna Methylation Signatures As Biomarkers In Circulationmentioning
confidence: 99%
“…In this study, circulating DNA (ctDNA) modifications collected from prostate cancer patients with locally confined disease (19 patients), in patients with benign prostate hyperplasias (20 patients), and in men without any known prostate disease (20 patients) were studied after isolation of ctDNA from plasma. DNA methylation in these ctDNA samples were studied via the bisulfite method [3]. The data showed that, when assayed via the analysis of ctDNA, the greatest difference between prostate cancer patients and controls was located at RNF219 (gene encoding ring-finger protein 219) on chromosome 13q31.1.…”
Section: Dna Methylation Signatures As Biomarkers In Circulationmentioning
confidence: 99%